Capital in The Twenty – First Century by Thomas Piketty: Book Review - Abulhul, Zeinab (Technium Social Sciences Journal, 2020)
In Capital in the Twenty-First Century, Thomas Piketty depicted the evolution of wealth distribution and explained the way aggregated and unequal distribution resulted in the escalation of the rate of inequality. Also, Piketty analyzed potential solutions for accumulation and distribution of wealth by considering historical data. Therefore, he tracked the historical publications of many economists who analyzed wealth distribution and inequality to understand the origin of the problem of wealth distribution inequality, such as Malthus’ Essay on the Principle of Population,1798, Ricardo’s principle of scarcity in Principles of Political Economy and Taxation,1817, Marx’s principle of infinite Accumulation in Capital, 1867, and Simon Kuznets’s Shares of Upper Income Groups in Income and Savings,1953. Piketty suggested a new taxation system is the solution to inequality in wealth distribution and to avoid unstable socio-economic trends. Piketty divided his book into four parts, and each part is comprised of chapters.